2016
DOI: 10.1021/acs.energyfuels.6b02165
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Research on the Effects of Coal Devolatilization and Char Combustion Processes on the Emission of Particulate Matter during Lignite Combustion under Air and Oxy-fuel Conditions

Abstract: The pulverized coal combustion in both air and oxy-fuel conditions generally experiences successive coal devolatilization and char combustion processes. The effects of these two processes have important influence on the emission characteristics of particulate matter. With some different characteristics of lignite from the higher rank coal, including the high contents of organically bound cations and the apparent char−CO 2 gasification reaction upon oxy-fuel combustion, the effects of both coal devolatilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It may be attributed to two reasons. First, in addition to the vaporization of refractory oxides/metals during char combustion, the release of organically bound metals associated with coal devolatilization may also play a substantial role in PM 1 formation. , , As the volatile matter content of the coal increases, therefore, more organically bound metals are likely to release during devolatilization to contribute in PM 1 formation. , Additionally, a coal with a higher rank index value generally produces the char with a higher reactivity during pulverized coal combustion . The resulting char may burn at a relatively higher temperature, favoring the vaporization of refractory oxides/metals to form more sub-micrometer ash.…”
Section: Discussionmentioning
confidence: 99%
“…It may be attributed to two reasons. First, in addition to the vaporization of refractory oxides/metals during char combustion, the release of organically bound metals associated with coal devolatilization may also play a substantial role in PM 1 formation. , , As the volatile matter content of the coal increases, therefore, more organically bound metals are likely to release during devolatilization to contribute in PM 1 formation. , Additionally, a coal with a higher rank index value generally produces the char with a higher reactivity during pulverized coal combustion . The resulting char may burn at a relatively higher temperature, favoring the vaporization of refractory oxides/metals to form more sub-micrometer ash.…”
Section: Discussionmentioning
confidence: 99%
“…This enables us to compare the PM emission characteristics of experimentally measured results from the combustion of the (Na+Si)-loaded coal with the calculated results, which are the sum of PM 10 emitted from the combustion of the Na-and the Si-loaded coal. Such comparison, as shown in Figure 3, reveals whether the interactions of a typical vaporized element (Na) and refractory element (Si) occurred during coal combustion affect the emission of PM 2.5 and PM 10 .…”
Section: Comparison Of Experimentally Measured and Calculatedmentioning
confidence: 99%
“…The emission of fine particulate matter (PM), to a great extent, is responsible for the severe haze problem suffered by most cities in China in recent years. , The source apportionment of the emission of PM with aerodynamic diameters of <2.5 μm (PM 2.5 ) in several megacities (e.g., Beijing, Nanjing, and Wuhan) in China indicates that coal combustion contributes to ∼20% of local PM 2.5 annually. It is thus of great importance to develop advanced technologies to control the emission of PM 2.5 from coal-fired power stations, which requires a thorough understanding of its formation mechanisms. Due to the complexity of the formation of PM 2.5 (and also PM with aerodynamic diameters < 10 μm, PM 10 ) during coal combustion, their emission/formation often depends on the properties of inorganic species in coals and local combustion conditions experienced by coal particles, and in other words, the inorganic and organic properties of coals. The significant effects of both inorganic properties and organic properties of coals on inorganic PM 10 have been confirmed in our previous study on the emission of inorganic PM 10 from included mineral matter during the combustion of three coals of various ranks .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle formation is enhanced at higher temperatures due to increased mineral vaporisation and environments with low oxygen to fuel stoichiometry produce less ultrafines [57]. In addition, Wen et al [61] recently reported that combustion under N 2 resulted in production of more particulates than combustion in CO 2 .…”
Section: Mechanisms Of Nanomaterials Formation In Cfamentioning
confidence: 99%